Analisis Penerimaan Website Kelurahan Rejasari Menggunakan Metode Technology Acceptance Model (TAM) - Elza Puspitasari; Darmansah Darmansah; Dwi Mustika Kusumawardani (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Rejasari Village is one of the villages in the West Purwokerto sub-district. There are 2 types of services in the village, namely online and offline. The application of the website in Rejasari Village has not been going well because the services contained on the website are not managed. The information contained on the website is not updated because the operator who manages the kelurahan website has limited time between jobs in the kelurahan. This requires an in-depth study of the acceptance of websites in Rejasari Village. Therefore, the factors that influence the acceptance of the Desa Rejasari website were investigated using the Technology Acceptance Models (TAM) method. The elements selected for the website acceptance analysis were perceived usability, perceived ease of use, intended use, and actual system usage elements. The results of this study are the factors that affect the acceptance of the website. The purpose of this study was to determine user acceptance of the Rejasari Village website. This supervision is carried out because user acceptance is one of the main factors affecting the implementation of a website. The sample used in this research is the community and village officials in the Rejasari village who know the Rejasari village website. This study used 49 respondents as the sample for this study. The results of this study indicate that the acceptance of the website in Rejasari Village must be considered is the factor of using the Rejasari Village website system.